Estimation of cancer incidence in the male population of the Altai Krai affected by the Semipalatinsk nuclear test - A. O. Kovrigin; V. A. Lubennikov; I. B. Kolyado; I. V. Vikhlyanov; A. F. Lazarev; Ya. N. Shoikhet (Сибирский онкологический журнал, 2022)
The purpose of the study was to analyze the cancer incidence in the males born from 1932 to 1949 and living in rural settlements of the municipal districts of the altai Krai affected by the traces from semipalatinsk first nuclear test on august 29, 1949. Material and methods. an epidemiological retrospective cohort study was based on the analysis of anonymized data on newly diagnosed and morphologically verified cases of cancer in a male cohort for the period from 2007 to 2016. the study included a cohort fixed by the date of the first nuclear test with a total of 6383 males. in total, 633 cases were identified in the cohort with newly diagnosed and morphologically verified cancer. at the beginning of the study, all males were alive and had no previous diagnosis of cancer. For a comparative analysis of the cancer incidence, the main (exposed) cohort comprised 2 291 men, and the control cohort included 4 092 men, who lived in rural settlements of municipal districts of the region and were not tracked during the first nuclear test conducted at the semipalatinsk test site. the person-time incidence rate (ptR), standard error (mptR) and confidence intervals (95 % ci) were calculated. the incidence and the relative risk of developing cancer were assessed. statistical analysis was carried out using microsoft office 2016. Results. the number of person-years in the main cohort was 1 6731 person-years, and in the control was 30 747. The incidence rate of person-time (ptR) in the main cohort was 2 032.22 × 105 person-years, with mptR equal to 110.21 and confidence intervals (95 % ci) – (1 811.80–2 252.64). in the control cohort, the corresponding values were: ptR – 952.94 × 105 person-years with mptR – 55,67 and 95 % ci (841.60–1 064.28). the most common cancer localizations in men of the main cohort were: digestive organs (c15-c26), respiratory and chest organs (c30-c39), skin (c43-c44), male genitals (c60-c63). in the control group, the most common localizations were respiratory and chest organs (c30-c39), digestive organs (c15-c26), male genital organs (c60-c63) and skin (c43-c44). Conclusion. an increased relative risk of developing malignant neoplasms in men born and living in the altai territory during the first nuclear test conducted at the semipalatinsk test site was revealed (RR=2.133; 95 % ci 1.824–2.493) with standard error of relative risk (s) equal to 0.0797. there were differences in cancer localization between the main and the control cohorts.